Type 2 diabetes and vascular complications: A pathophysiologic view - Ahmed, K.A.A.; Muniandy, S.; Ismail, I.S. (2010)
Diabetes mellitus (DM) represents a range of metabolic disorders characterized by hyperglycemia resulting from insulin deficiency or insulin resistance or both. Hyperglycemia, the primary clinical manifestation of diabetes, is strongly associated with development of the diabetic complications. Complications caused by hyperglycaemia involve damage to the small vessels such as in neuropathy, nephropathy, and retinopathy, and large blood vessels as in cardiovascular diseases. It is well known established that in diabetes, long-term complications ensue from abnormal regulation of glucose metabolism. In fact, all manifestations of cardiovascular disease, coronary heart disease, stroke and peripheral vascular disease are substantially more common in patients with type 2 diabetes than in non-diabetic individuals. For example, patients with type 2 diabetes (T2DM) have a two-to fourfold increased risk of fatal and non-fatal coronary events. Diabetes can lead to microvascular and macrovascular damage through a number of mechanisms, each of which may worsen or accelerate the others. The present review summarizes the information on the mechanisms of how vascular complications will develop in type 2 diabetes and this might be useful as a direction for further research to provide new strategies for prevention and treatment of these complications in their early stages.